Optimasi Branding Produk UMKM dan Peningkatan Popularitas Hutan Telagasari Sebagai Destinasi Wisata Lebah Madu di Kota Balikpapan - Rifqiandi, Muhammad; Harli Andrika Lomo; Muhammad Noor Ihsan Fadhilah; Amalia Kartika; Rangga Hermawa; Paulus Anthony Zejlstra; Desilya Lau; Mujahidin, Syamsul; Tama, Yanuar Bhakti Wira (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Telagasari Urban Forest, as a unique kerangas forest ecosystem in Kalimantan, holds significant potential in economic, ecological, and social aspects through sustainable management and honey bee cultivation. However, limited digital promotion constrains the utilization of this potential. A community engagement program in RT 45, Telagasari, Balikpapan, aimed to enhance the digital marketing skills of local MSMEs and develop the educational tourism site "Karamunting Honey Bee Tourism." Activities included training in copywriting, content strategy, and digital marketing, followed by hands-on practice, as well as promoting educational tourism for students. Results indicated that digital marketing training effectively improved participants' skills, with a satisfaction level of 87% post-program. Additionally, the development of the honey bee tourism site was supported by an informational website and QR codes on vegetation, enhancing information accessibility and tourism appeal. This program demonstrates that synergy between natural resource utilization and digital strategies can support local product branding while raising environmental conservation awareness.